The Effectiveness of Communication Strategies in Sexuality Education for Preventing Sexual Abuse among Elementary School Students - Lestari, Desi Yani; Sari, Afrina (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2026)
This study aims to examine the effectiveness of communication strategies used in sexuality education programs in improving elementary school students’ understanding of self-protection against sexual abuse. The research was conducted at SDN 1 Bojongkerta Sukabumi, West Java, Indonesia, using a quantitative approach with a one-group pretest–posttest design. A total of 21 sixth-grade students, who completed both the pretest and posttest, were selected through purposive sampling. The data were analyzed using the Wilcoxon Signed-Rank Test with a significance level of 0.05. Only one indicator the ability to distinguish between appropriate and inappropriate touch showed a statisticslly significant improvement (Z = -2.100; p = 0.036), while the remaining indicators, across eight measured indicators, including the ability to refuse uncomfortable touch (p = 0.480) and willingness to report to trusted adults (p >.999), did not show significant differences between pretest and posttest scores. These findings indicate that the communication strategies applied were only partially effective, particularly in improving students’ cognitive understanding of the concrete concepts. However, they were less effective in influencing broader behavioral and emotional aspects, which require continuous reinforcement and repeated exposure. This study highlights the importance of developing sustained and interactive communication strategies in sexual education programs to achieve more comprehensive behavioral change among elementary school students.